Numerical investigation on the effect of infill walls and the short column effect on the structural performance of reinforced concrete frames - Sia, Garret Wilkenson C. (Animo Repository, 2022)
In the Philippines, reinforced concrete (RC) frames with concrete hollow block (CHB) infill walls are among the most common low-rise constructions. However, infill walls are usually considered as nonstructural and are not included in design models, yet infill walls may negatively affect the seismic performances of frames. For instance, in earthquakes, shear stresses concentrate in free portions of columns restrained by stiff partial-height walls, hence the short column effect. When these columns are not designed to resist the shear increase induced, columns experience shear failure. In this study, using nonlinear static pushover analysis, a five-story RC frame was fully and partially infilled. Different infill configurations, heights, and thicknesses were used to examine their effects on the building seismic performance. When partial-height walls populated all exterior faces, base shears were less than the reference bare frame. Hinge models also showed that such layout resulted in short column shear hinges in partially restrained columns. Column shears were also found to increase by at least 180% with respect to the bare frame model. Increases in infill height also resulted in increased short column shear hinges and decreased base shears. Nevertheless, when infill heights less than 40% of the height of the adjacent column were considered, the short column effects induced were relatively tolerable based on the global seismic performances. Moreover, analyses showed that 250-mm walls induced increased short column shear hinge formation and lower base shear capacity, while 200-mm walls induced better performance because of reduced column restraint. The study thus recommended imperative consideration of masonry infills, especially partial-height walls, in design processes to recognize and address behaviors such as the short column effect, so that columns expected to experience the induced short column effect must then be sufficiently designed or retrofitted to resist increased shear demands.